Analysis of the Implementation of Project Control Information System (SIPP) in Engineering Procurement Construction Projects - Rudi Iryanto; Arviansyah Arviansyah (Management Analysis Journal, 2023)
Information System is a system that is needed by organizations in evaluating the performance of a project. In EPC projects, tools are needed to help evaluate costs and progress. For this reason, through the Project Control Information System (SIPP), the prognosis of costs and project progress can be known. This study uses a mix method that aims to analyze the performance of SIPP in the Sorong Open Access project by comparing the Financial Work Plan (RKK) report with data inputted in the SIPP system and interview methods to users, direct supervisors and upper management. So that a conclusion and recommendations can be produced for improving data input and the use of SIPP in EPC projects. The results of quantitative research that have been carried out on the percentage of suitability of cost item data and RKK progress items inputted in the SIPP in December 2022, January 2023 and February 2023 the conformity value is still small. The results of qualitative research from interviews of 12 people represented by 5 users, 4 user superiors and 3 upper management, concluded that the SIPP program was quite good. However, improvements are needed in the data verification process after input. The proposed new business process is expected to improve the data input process and the conformity of the input data is 100%. So that payment problems to suppliers and progress do not experience obstacles due to data discrepancies in SIPP.